2007
DOI: 10.1159/000111929
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Exercise Capacity in Diabetic Patients after Coronary Bypass Surgery: Effects of Diastolic and Endothelial Function

Abstract: Objectives: The aims of this study were to clarify the influence of cardiac diastolic and peripheral vascular function on the exercise capacity of patients with coronary bypass surgery (CABG) and diabetes mellitus (DM) by tissue Doppler imaging (TDI) and flow-mediated vasodilatation (FMD), and to investigate interrelations between exercise capacity and LV diastolic function, endothelial function and biochemical parameters. Methods: We analyzed the exercise capacity, TDI at the mitral annulus and FMD in 51 unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 83 publications
2
12
1
Order By: Relevance
“…The increased risk that diabetes poses for CHF in women compared with men was confirmed in the recent Heart and Estrogen Replacement Study [7] in which diabetes emerged as the strongest risk factor for CHF in women with coronary disease. This has not been shown in the study by Wu et al [1] . Thus, females suffer more often from CHF when compared with male diabetics.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The increased risk that diabetes poses for CHF in women compared with men was confirmed in the recent Heart and Estrogen Replacement Study [7] in which diabetes emerged as the strongest risk factor for CHF in women with coronary disease. This has not been shown in the study by Wu et al [1] . Thus, females suffer more often from CHF when compared with male diabetics.…”
contrasting
confidence: 53%
“…In their study 'Impaired exercise capacity in diabetic patients after coronary bypass surgery: effects of diastolic and endothelial function', Wu et al [1] have demonstrated that diabetics after coronary artery bypass graft (CABG) had more advanced diastolic dysfunction and oxygen extraction impairment than non-diabetic patients.…”
mentioning
confidence: 99%
“…Decreased O 2 delivery may occur in diabetic patients with HFpEF due to a greater prevalence of anemia (a trend was seen in our data) or less vasodilator reserve due to autonomic dysfunction, an increased prevalence of peripheral vascular disease, or impaired endothelial function from oxidative stress, inflammation, and vasoconstriction (consistent with the biomarker elevations we observed in diabetic patients with HFpEF). Abnormalities in oxygen delivery and extraction have been observed in diabetic patients (28,29). …”
Section: Discussionmentioning
confidence: 99%
“…Limitations on cardiac reserve and cardiac contractile function thus restrict the supply from meeting the demand imposed by exercise. In addition, microcirculatory deficits coupled with altered energetics limit the ability to meet the demand in exercising skeletal muscle in diabetics 15 16. Endothelial dysfunction and functional alterations of the microcirculation, on the other hand, precede morphological changes and contribute to an increased vascular permeability17 and an impaired endothelial vasodilatory response.…”
Section: Discussionmentioning
confidence: 99%